Faktor yang Mempengaruhi Keberlanjutan Budidaya Padi IP400 di Kabupaten Sukoharjo - Eullia Tri Mukti Hezak; Suminah Suminah; Widiyanto Widiyanto (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Sukoharjo Regency, in 2022, managed to receive the Muri Record Award for the most extensive IP400 land holding in Indonesia. The continued adoption of this rice cultivation type did not follow the program ending in the same year. This research is then being conducted to determine the factors affecting the sustainability of IP400 rice cultivation adoption, especially in Bendosari District, Sukoharjo Regency. This research has three objectives, and there are: 1) to analyze IP400 rice cultivation sustainability in Sukoharjo, 2) to analyze the distribution of respondents toward factors affecting IP400 rice cultivation sustainability in Sukoharjo, and 3) to analyze the factors affecting IP400 rice cultivation sustainability in Sukoharjo. This research used four variables and there is farmers' perception of the IP400 program (X1), extension assistance in the IP400 program (X2), the availability of production input in the IP400 program (X3), and innovation characteristic of the IP400 rice cultivation (X4). This research used exploratory quantitative methods and was conducted in Bendosari District, Sukoharjo Regency, from April 2024 until May 2024, with 85 respondents. Data analysis used logistic regression techniques with SPSS 25 analysis tool. The result of this research was two variables that significantly affect the likelihood of sustainable adoption of IP400 rice cultivation, and there is farmers' perception of the IP400 program (X1) and innovation characteristic of the IP400 rice cultivation (X4). This research suggests: 1) evaluating policy recommendations for IP400 cultivation, especially in terms of technical aspects in increasing rice productivity related to relative advantage obtained by farmers and compatibility to the land itself, and 2) procurement of wetlands selection with high compatibility for IP400 cultivation to ensure optimal results and ensure more profits for farmers, both in economic and technical terms of rice cultivation.